Uterine Artery Embolization (UAE) for Fibroid Treatment – Results of the 7th Radiological Gynecological Expert Meeting - Kröncke, Thomas; David, Matthias (Geburtshilfe und Frauenheilkunde, 2019)
Uterine artery embolization (UAE) is a safe and effective organ sparing treatment for fibroid-related symptoms based on a broad range of published evidence including randomized-controlled trials. Indication for treatment by means of UAE are symptomatic uterine fibroids. UAE is an alternative to surgical and medical treatment for uterine fibroids as well as treatment by MRgFUS. This consensus paper covers the structural prerequisites, the criteria for technical and clinical success, contraindications, side effects and complications as well as the role of UAE treatment in women wishing to conceive and gives guidance on radiation safety measures and clinical follow-up.Die Uterusarterienembolisation (UAE) ist ein organerhaltendes Verfahren zur Behandlung myombedingter Beschwerden, dessen Sicherheit und Effektivität durch eine breite Evidenz einschließlich randomisiert-kontrollierter Studien abgesichert ist. Die Indikation für eine UAE zur Myombehandlung (Myomembolisation) ist ein symptomatischer Uterus myomatosus. Die UAE stellt eine Alternative zur operativen und medikamentösen sowie zur Myomtherapie mittels fokussiertem Ultraschall dar. Das Konsensuspapier stellt die strukturellen Voraussetzungen, die Erfolgskriterien, die Kontraindikationen, mögliche Nebenwirkungen sowie die Rolle der UAE bei Kinderwunsch dar und gibt Empfehlungen zum Strahlenschutz und zu Nachuntersuchungen.
Keywords: uterus; embolization; leiomyoma; uterine artery embolization